INOVASI TEKNOLOGI PENERAPAN KOMPOS BLOTONG UNTUK PERBAIKAN KESUBURAN TANAH DAN PENINGKATAN PRODUKTIVITAS TANAMAN TEBU - Muh Afif Juradi; Edi Tando; Saida Saida (Percetakan Umi Toaha Makassar, 2020)
Sugarcane (Saccharum officinarum L.) is a variety of sources of carbohydrate as sugar production. Planting of sugar cane monoculture and continuously in dry land causes degradation of soil fertility. One effort to improve soil fertility is the addition of organic matter. through the use of blotong compost. The purpose of this paper is to provide information on blotong compost technology innovation in improving soil fertility and increasing sugarcane productivity.Blotong has potential as a source of organic material from the residual waste from sugarcane crop yields. The macro and micro nutrient content of compost in blotong compost plays an important role in supporting plant growth. Blotong compost application in the long term can increase the physical, biological and chemical fertility of degraded land. Blotong compost application with inorganic fertilizer can reduce the use of inorganic fertilizer. Blotong application can increase the nutrient content of N, P and micro elements in the soil and can increase the growth and productivity plant sugarcane.